Une exposition à l’échelle de la ville - Laurence Brogniez; Tatiana Debroux (Contextes)
This article deals with the places complementary to the ‘Salons’ of the XX and La Libre Esthétique at the turn of the 20th century, and the sociabilities organized around these exhibitions in Brussels. By adopting a spatial perspective based on an inventory of residential addresses of artists and art lovers, and the different types of places where they met inside and outside Brussels, we tried to identify and define the spaces of sociability of an artistic avant-garde that is nowadays well studied aesthetically, but rarely from a geographical point of view. The cartographic results presented here offer a synthesis of the sociabilities of the XX and their successors, combining material and symbolic aspects through the spaces chosen to live, create and to be seen. Through an overall analysis and the presentation of a few key places, we tried to show how these spaces generated original worldly practices that participated in the abolition of the separation between living and working places, between exhibition and representation spaces. The ‘Salon d’art’ adopting the scenography of the private salon and the latter hosting exhibitions, a new relationship with the work of art and a new aesthetic experience emerge in the wake of the XX.